Collins COBUILD phrasal verbs dictionary - Gautier, Phyllis; Macaulay, Alison; Seaton, Maggie (Glasgow : HarperCollins, 2011)
This reissue of the second edition of the Collins COBUILD Dictionary of Phrasal Verbs offers comprehensive coverage of the most important phrasal verbs in English
"Collins corpus"--Cover
Originally published: 2002
1 10
Keywords: English language -- Verb phrase -- Dictionaries